Immune Benefits of Consuming Red Muscadine Wine - Susan S. Percival; Charles A. Sims; Stephen T. Talcott (EDIS, 2002)
This document is FSHN02-4, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: September 2002.